A Smart Metal–Organic Framework Nanomaterial for Lung Targeting. (2nd November 2017) - Simon‐Yarza, Teresa; Giménez‐Marqués, Mónica; Mrimi, Rhizlaine; Mielcarek, Angelika; Gref, Ruxandra; Horcajada, Patricia; Serre, Christian; Couvreur, Patrick
Abstract: Despite high morbidity and mortality associated with lung diseases, addressing drugs towards lung tissue remains a pending task. Particle lung filtration has been proposed for passive lung targeting and drug delivery. However, toxicity issues derived from the long‐term presence of the particles must be overcome. By exploiting some of the ignored properties of nanosized metal–organic frameworks it is possible to achieve impressive antitumoral effects on experimental lung tumors, even without the need to engineer the surface of the material. In fact, it was discovered that, based on unique pH‐responsiveness and reversible aggregation behaviors, nanoMOF was capable of targeting lung tissue. At the neutral pH of the blood, the nanoMOFs form aggregates with the adequate size to be retained in lung capillaries. Within 24 h they then disaggregate and release their drug payload. This phenomenon was compatible with lung tissue physiology.